Novel Multi-Modal Analgesia Protocol Significantly Decreases Opioid Requirements in Inflatable Penile Prosthesis Patients. Issue 8 (15th July 2018) - Tong, Ching Man Carmen; Lucas, Jacob; Shah, Ankur; Foote, Christopher; Simhan, Jay
Abstract: Background: Inflatable penile prosthesis (IPP) surgery is associated with significant perioperative pain that may reduce patient satisfaction. Though various pain management strategies have been proposed, most implanters manage postoperative patients with only prescription opioids. No protocol to date has been implemented and reported for pain management in IPP patients throughout the entire recovery process following surgery. Aim: Develop a multimodal analgesic (MMA) regimen consisting of perioperative administration of acetaminophen, meloxicam, and gabapentin with intraoperative local anesthetic injections, and compare post-operative pain control to a matched cohort of patients managed with an opioid-based (OB) regimen. Methods: We retrospectively analyzed our prospectively maintained IPP database from November 2015–January 2018. The MMA protocol was instituted for all patients beginning June 2017, and these patients were matched in a 1:2 ratio to a cohort of eligible IPP patients managed through an OB protocol. Only patients receiving a 3-piece IPP were included; those with a history of narcotic dependence, neuropathy, or chronic non-steroidal anti-inflammatory drug use were excluded. Postoperative pain scores (visual analog scale) and opioid usage (total morphine equivalents [TME] in milligrams) were compared temporally in the post-anesthesia care unit, postoperative day (POD) 0, POD 1, and following discharge. Outcomes: The primary outcomes of the study are postoperative pain scores and narcotic usage. Results: 57 patients were eligible for analysis: 19 (33%) and 38 (66%) in the MMA and OB groups, respectively. Groups were similar in demographics. MMA patients had significantly lower visual analog scale scores in post-anesthesia care unit, POD 0, or POD 1 (mean 0.84 vs 2.97, P = .01; 2.62 vs 4.73, P = .003; and 2.26 vs 4.0, P = .01, respectively) and used fewer narcotics on POD 0 (mean 4.08 vs 13.8 mg TME, P < .001) and POD 1 (mean 5.05 vs 25.1 mg TME, P < .001). MMA patients were discharged home with fewer narcotics (mean 12.7 vs 51.3 tabs, P < .001), and despite this, the MMA group needed less narcotic medication refills (11% vs 49%, P = .007). Neither group experienced a medication-related postoperative adverse event. Clinical Implications: Multimodal pain management allows for effective pain control with minimal side effects, enhancing recovery. Strengths & Limitations: This is the first report to assess use of a multi-modal pain regimen on IPP recipients with demonstration of tangible benefit throughout the recovery process. Limitations include a single-surgeon and retrospective study design. Conclusion: In our rigorous assessment of IPP patients, implementation of a novel MMA protocol achieved equivalent and effective pain control, while resulting in substantially fewer narcotics throughout the entire post-operative period following IPP implantation.